The role of the respiratory microbiome in asthma - Christina D. Campbell; Margaret Gleeson; Imran Sulaiman; Imran Sulaiman (Frontiers in Allergy, 2023)
Asthma is a common airways disease and the human microbiome plays an increasingly recognised role in asthma pathogenesis. Furthermore, the respiratory microbiome varies with asthma phenotype, endotype and disease severity. Consequently, asthma therapies have a direct effect on the respiratory microbiome. Newer biological therapies have led to a significant paradigm shift in how we treat refractory Type 2 high asthma. While airway inflammation is the generally accepted mechanism of action of all asthma therapies, including both inhaled and systemic therapies, there is evidence to suggest that they may also alter the microbiome to create a more functionally balanced airway microenvironment while also influencing airway inflammation directly. This downregulated inflammatory cascade seen biochemically, and reflected in improved clinical outcomes, supports the hypothesis that biological therapies may in fact affect the microbiome-host immune system dynamic and thus represent a therapeutic target for exacerbations and disease control.